Effectivity of Spodoptera littoralis Nucleopolyhedrovirus (SpliMNPV) and Natural Additives Mixtures against Spodoptera litura Fab. (Lepidoptera: Noctuidae) on Cabbage Plants - Sukirno Sukirno; Bellia Alda Ayu Prasetya; Aryo Seto Pandu; Siti Sumarmi; Hari Purwanto; Ignatius Sudaryadi; Suparmin Suparmin; RC Hidayat Soesilohadi (Journal of Tropical Biodiversity and Biotechnology, 2022)
Armyworm (Spodoptera litura Fab.) is one of the agricultural pests that can cause huge losses especially for Indonesian farmers because it is damaging various crops, especially cabbage (Brassica oleifera L.). Spodoptera littoralis nucleopolyhedrovirus (SpliMNPV) is one of the biological agent which is effective for the management of the Spodoptera litura. However, because of UV radiation it easily degraded when applied in the fields. This study was aimed to determine the effectivity of several indigenous plants for UV protectant of SpliMNPV for controlling armyworm at greenhouse scale. Extracts of 2% (w/v) of turmeric rhizome, red betel leaf, moringa leaf, and clove flower, were formulated with SpliMNPV and sprayed evenly onto two-month- old cabbages. The experiment used five replicates with six periods of sunlight exposures (0, 1, 3, 5, 7, and 15 days). A commercial product of deltamethrin was used as a comparison. The sprayed leaves were then used as a bioassay by using 25 individuals of one day old 1st larval instar by five replicates. The results showed that the turmeric additive was the most effective as a UV protectant and effectively prolonged the half-life of SpliMNPV to 4.12 days, while for clove, moringa leaf, and red betel was 2.48, 2.15, and 2.28 days, respectively.